Irradiation Effects on The Sensitivity of ZnO Thin Films Synthesized on Glass Substrate by Sol-gel Method - Kasim, Yasir Yahya; Ali, Ghazwan Ghazi; Younus , Marwan Hafeedh (Iraqi Journal of Science, 2021)
This work investigates the structural, optical, and surface properties of ZnO thin films prepared by sol-gel method. The effect on waveguide sensor was examined at different irradiation durations of alpha particles. The X-ray diffraction (XRD) measurements revealed that the crystalline phase of ZnO thin films does not change after irradiation and showed a hexagonal structure of wurtzite type with an orientation toward (002). Moreover, ZnO thin films absorbance was increased with increasing irradiation time, whereas the transmittance was decreased. Additionally, increasing the irradiation time of alpha particles caused an increase in the extinction coefficient and the imaginary part, while the optical energy gap of the ZnO samples was decreased. Finally, the maximum value of sensitivity was 42%, found at 6 min of irradiation duration.